2022
DOI: 10.1186/s12884-022-05228-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ionophore improves embryonic development and pregnancy outcomes in patients with previous developmental problems in ICSI cycles

Abstract: Background Calcium (Ca2+) ionophores are now mainly considered as efficient treatments for fertilization failure. Recently, its application for rescuing poor embryo development was proposed but still non-routine. This study aimed to explore whether Ca2+ ionophore improves embryo development and pregnancy outcomes in patients with poor embryo development in previous intracytoplasmic sperm injection (ICSI) cycles. Methods This study included 97 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, our sample population is the largest of any study conducted on this subject to date. Some clinical studies and meta-analyses have reported that AOA may help improve fertilization, embryonic development, and clinical pregnancy outcomes in many clinical conditions [21,23]. Therefore, we performed AOA mostly in patients with poor prognoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our sample population is the largest of any study conducted on this subject to date. Some clinical studies and meta-analyses have reported that AOA may help improve fertilization, embryonic development, and clinical pregnancy outcomes in many clinical conditions [21,23]. Therefore, we performed AOA mostly in patients with poor prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have attempted to improve the clinical outcomes of patients who experience fertilization failure or low fertilization rates using arti cial oocyte activation (AOA), including the use of PLCz and arti cial activators such as Ca ionomycin, Ca ionophore (A23187), strontium chloride, electrical pulse activation, and mechanical activation [20]. According to studies and meta-analyses, Ca ionophore (Cai) application signi cantly improves the overall fertilization rates in patients who experience fertilization failure [21][22][23]. Positive effects of Cai application have been detected at various embryonic development stages [19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, during these stages, calcium ions modulate the release of vital secondary messengers, including inositol trisphosphate (IP3) [33], cyclic adenosine monophosphate (cAMP) [34], and diacylglycerol (DAG) [35], which are essential for oocyte activation and its fusion with the spermatozoon [31,32]. In the early stages of embryonic development, a balanced calcium concentration is crucial for proper cellular division and the implantation of the embryo into the uterine lining [31,[200][201][202][203]. Consequently, an imbalance in calcium levels, whether due to a deficiency [204,205] or excess [206], can compromise fertility and reduce the likelihood of a successful pregnancy [207].…”
Section: Calciummentioning
confidence: 99%
“…Furthermore, the Leukemia Inhibitory Factor (LIF) is another crucial molecule linked to embryo development [377]. Overall, these results indicate that an adequate calcium level in the body is a requirement for the successful implantation of the embryo and the initiation of pregnancy [45,203,370,378].…”
Section: Calciummentioning
confidence: 99%